2007
DOI: 10.1007/s10508-007-9282-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Fluctuating Asymmetry in Men and Women

Abstract: Previous research suggests that individuals' sexual orientation may be affected by developmental instability (DI) induced by exposure to prenatal stresses. We tested this relationship using fluctuating asymmetry (FA), the small random deviations from symmetry that arise in otherwise bilaterally symmetrical traits as a consequence of developmental noise and developmental instability. Differences among individuals reflect variation in their exposure to and ability to accommodate for stresses experienced during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
4
14
1
Order By: Relevance
“…Our results suggested that 2D:4D of homosexual men was significantly higher compared to that of heterosexual men. This result supports the findings of some previous work on the relationship between 2D:4D and male sexual orientation (e.g., Hall & Schaeff, 2008;Lippa, 2003;Manning et al, 2007) suggesting that low prenatal androgen exposure in particular may be associated with homosexuality in men (Collaer & Hines, 1995;Ellis & Ames, 1987;Rahman & Wilson, 2003a).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results suggested that 2D:4D of homosexual men was significantly higher compared to that of heterosexual men. This result supports the findings of some previous work on the relationship between 2D:4D and male sexual orientation (e.g., Hall & Schaeff, 2008;Lippa, 2003;Manning et al, 2007) suggesting that low prenatal androgen exposure in particular may be associated with homosexuality in men (Collaer & Hines, 1995;Ellis & Ames, 1987;Rahman & Wilson, 2003a).…”
Section: Discussionsupporting
confidence: 91%
“…This result supports the findings of some previous studies (Hall & Schaeff, 2008;Hiraishi et al, 2012;McFadden & Shubel, 2002), but conflicts with other work (Lippa, 2003;Manning et al, 2007). Manning et al (1998) suggested that the right hand 2D:4D is likely to reflect prenatal androgen exposure more strongly than the left hand.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, Rahman (2005) analyzed a composite index consisting of nine traits, which may have obscured more subtle effects. Further, Hall and Schaeff (2008), who also assessed some of the same traits we did, reported that mean FAs were higher among gay men on four of seven traits plus the composite index and among lesbians on five of seven traits and the composite index when compared with heterosexuals. Considering the inconsistency in the data examining the relationship between handedness and sexual orientation, the lack of agreement among the studies examining other indices of DI is not surprising.…”
Section: Discussionsupporting
confidence: 54%